The environmental challenge: teachings with COVID-19 as a starting point - Liliana María Gomez Luna (Centro Provincial de Información de Ciencias Médicas, 2020)
The environmental questions are linked to the emergency of epidemics. The crisis that world faces today has had its origin in the constant environmental interferences, what has been reflected in the concerns manifested by the United Nations Organization in each celebration of the Environment World Day. The degraded ecosystems cannot offer ecological services that guarantee well-being and health; this way, a crisis takes to another. In this work it is exposed how men are exposed to more than a million of unknown pathogens microorganisms that could cross the barrier of the species when breaking the natural balance that protects him of multiple risks, such is the case of the SARS-CoV-2 new virus; this comes on top of the threat of the climatic change that is an instigator of many risks. Health problems will always be subject to the interaction of each civilization with their environment, what depends, in essence, of the character in man-nature relationship.